Answer:
x = 5
y = -2
Step-by-step explanation:
2x + y = 8
y= x - 7
We need are solving for x, and we know what y is
We need to substitute the y equation for y in the first equation
2x+x-7=8
Step 1: Simplify both sides of the equation.
2x+x−7=8
2x+x+−7=8
(2x+x)+(−7)=8(Combine Like Terms)
3x+−7=8
3x−7=8
Step 2: Add 7 to both sides.
3x−7+7=8+7
3x=15
Step 3: Divide both sides by 3.
3x / 3 = 15 / 3
x = 5
Solve for y
2x + y = 8
2 * 5 + y = 8
Step 1: Simplify both sides of the equation.
(2)(5)+y=8
10+y=8
y+10=8
Step 2: Subtract 10 from both sides.
y+10−10=8−10
y=−2